2010
DOI: 10.1093/chromsci/48.6.484
|View full text |Cite
|
Sign up to set email alerts
|

A Single Reversed-Phase UPLC Method for Quantification of Levofloxacin in Aqueous Humour and Pharmaceutical Dosage Forms

Abstract: An attempt was made to develop a single, rapid, specific, and sensitive gradient reversed-phase ultra-performance liquid chromatographic method for quantitative analysis of levofloxacin. The single method thus developed is applied for the quantification of levofloxacin both in aqueous humour as well as pharmaceutical dosage forms (i.e., tablets and eye drops). The newly developed method is applicable for pharmacokinetic studies of eye formulations. The chromatographic separation of levofloxacin was achieved on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…This method gives the possibility to evaluate potency and monitor the biological activity of voriconazole in patients (32). Voriconazole level in plasma, following the administration of multiple oral or intravenous doses, varies from 1.0 to 5.5 µg/mL (20,33), which are within the limits in which the bioassay method was linear (0.25 -16 µg/mL) in this study.…”
Section: Discussionsupporting
confidence: 54%
“…This method gives the possibility to evaluate potency and monitor the biological activity of voriconazole in patients (32). Voriconazole level in plasma, following the administration of multiple oral or intravenous doses, varies from 1.0 to 5.5 µg/mL (20,33), which are within the limits in which the bioassay method was linear (0.25 -16 µg/mL) in this study.…”
Section: Discussionsupporting
confidence: 54%
“…The stock solutions of the new fluoroquinolones, used for the validation of liquid chromatographic methods, have been prepared in several solvents: water, methanol, acetonitrile and a mixture of water/methanol or water/acetonitrile [54][55][56][57][58]. In some cases, to deviate from neutral pH and thus enhance solubility in water, a basic solution (NaOH) was added in the preparation of LEV and SPA stock solutions, whereas for GAT, MOX, TRO and ULI an acid (HCl, formic acid, orthophophoric acid) or a phosphate buffer at pH 3 were also used [59][60][61][62][63][64][65].…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 99%
“…In the case of LEV, Gupta et al [58] found minimal drug degradation in 1 N HCl and considerable drug degradation under oxidation with 30% H 2 O 2 and under reduction conditions with 10% of Na 2 S 2 O 5 , always at room temperature. Gupta et al [73] achieved similar results for SPA although the samples were submitted to the above conditions for different times (8 h as opposed to 12 h in the case of LEV).…”
Section: Physicochemical Properties and Stability Of Fluoroquinolonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other studied drugs are not official in either pharmacopoeia. Non official methods reported for the determination of the studied drugs included titrimetric (Kiliç et al, 1994;, spectrophotometric (Fratiniand Schapoval, 1996;Abdel-Gawad et al, 1998;Rajasekaran et al, 1998;Basavaiahand Prameela, 2002;El-Brashy et al, 2004;El-Brashy et al, 2005;Al-Momani, 2006;Sultan, 2009;Siddiqui et al, 2010;Jain et al, 2011;Ayad et al, 2012;ElHawaryand Al-Gethami, 2012;Tarkase et al, 2012), Spectrofluorimetric (Jelikić-Stankov et al, 1999;Navalón et al, 2000;Rizk et al, 2000;El-Kommos et al, 2003;Salem, 2005;Kaur et al, 2010;Shah et al, 2013), electrochemical (Belaland ElDin, 1990;Tamer, 1990;Avsecand Gomišček, 1992;Ni et al, 2006), IR (Parent et al, 2004), NMR (Sakai et al, 1999), separation techniques (Wang et al, 1997;Schenckand Callery, 1998;Fierens et al, 2000;González et al, 2005;Gupta et al, 2010;Sousa et al, 2012). Recently, noble metal nanoparticlesbased UV-visible spectrometric methods have drawn special attention for selective and sensitive reorganization of target species (inorganic, organic and biomolecules) in various complex matrices (Vilela et al, 2012).…”
Section: Introductionmentioning
confidence: 99%